2012
DOI: 10.3233/ica-2012-0404
|View full text |Cite
|
Sign up to set email alerts
|

Detection and classification of road signs for automatic inventory systems using computer vision

Abstract: This article describes an intelligent system that enables the automatic recognition of road signs from image sequences in road environments. The main difficulties the system has to deal with are related to changes in lighting conditions, obstacles blocking the view, the presence of objects with geometric and chromatic similarities and the absence of previous knowledge about their position and orientation. The application of different techniques allows the system to overcome this variety of problems. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The existing approaches can be divided into three categories (Yin et al, 2015). In the first class, preprocessing methods are oriented to locate and recognise the traffic signs (Coronado et al, 2012) (Larsson & Felsberg, 2011). These methods require lots of preprocessing of the traffic images, and their generalisation capability and robustness are limited.…”
Section: Related Workmentioning
confidence: 99%
“…The existing approaches can be divided into three categories (Yin et al, 2015). In the first class, preprocessing methods are oriented to locate and recognise the traffic signs (Coronado et al, 2012) (Larsson & Felsberg, 2011). These methods require lots of preprocessing of the traffic images, and their generalisation capability and robustness are limited.…”
Section: Related Workmentioning
confidence: 99%
“…Therein, L denotes the luminance, and a and b denote the color. Coronado [ 8 ] develops an intelligent system to achieve automatic traffic sign recognition in terms of dealing with the difficulties that arise from changes in lighting conditions and various obstacles. Hu [ 9 ] achieves the traffic sign detection based on the visual attention model.…”
Section: Related Workmentioning
confidence: 99%
“…With this consideration, the capability of clarifying phases or states of traffic flows becomes a key in vehicle classification problems. Although tremendous studies have been reported on modeling traffic flow characteristic through multiple data sources (e.g., loops, video sensors, and floating vehicles) (Treiber and Kesting, 2011;van Lint and Hoogendoorn, 2010;Huang, 2010, 2012;Peláez Coronado et al, 2012), a challenge remains in identifying traffic phases by using the variables that could be directly calculated from the dual-loop data. Accordingly, two research problems inspired the authors' motivation to develop an empirical approach to innovate the length-based vehicle classification modeling and relevant computational algorithm against varied traffic flow phases at dual-loop detection stations.…”
Section: Introductionmentioning
confidence: 99%